(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Educational specialization is the sum of knowledge, skills and abilities acquired by a graduate during his studies. professional programs provide higher education and the opportunity to engage in certain types of professional activity in accordance with the qualifications obtained. Is there a fundamental difference between a field of study and a major? It should be noted that the educational direction provides a wider range of professional activities. There are also concepts such as "group of specialties" and "field of knowledge" - the division of sciences into certain types (humanitarian, technical, natural, educational, etc.). However, this difference is characteristic only for higher education. vocational education. What does the concept of "qualification in the field of study or specialty" mean? The level of preparation for the implementation of a certain type of professional activity in a certain field or specialty. Qualifications are determined by the State Educational Standard of Higher Vocational Education. The minimum wage also depends on the qualification (if you work in a public institution in your specialty).